202 Does NPM1 Mutation Have More Impact Than FLT3 on Response to Induction Chemotherapy in African-American Patients With Acute Myeloid Leukemia?. (11th January 2018) - Jayakumar, Rajeswari; Haseeb, MA; Gupta, Raavi
Abstract: Introduction: Fms-related tyrosine kinase 3 (FLT3) mutation, which is considered a poor prognostic marker, is identified in 25%-45% of patients with acute myeloid leukemia (AML), and nucleophosmin (NPM1) mutation, which predicts a favorable outcome in the absence of FLT3 mutation, has been identified in approximately 35% of patients with AML. The relevance of these mutations to induction chemotherapy (IC) outcomes in African-American patients has not been studied. Materials and Methods: Twenty consecutive cases of AML were identified and their records reviewed for clinical and laboratory data, treatment, and its outcomes. Data for karyotypic analysis, fluorescent in situ hybridization studies, and mutational analysis for FLT3 and NPM1 (performed on bone marrow) were collected. Results: FLT3 mutation was present in six of 20 AML patients, and NPM1 mutation was present in four of 20 AML patients. Thirteen of the twenty patients did not achieve remission after induction chemotherapy. The four (4/6) patients with sole FLT3 mutation were unresponsive to IC irrespective of favorable karyotype t(8;21) in a patient, and the other two (2/6) patients with additional NPM1 mutation showed complete response to IC. Of the 14 patients negative for FLT3 mutation, the two positive for NPM1 mutation showed complete response to IC in spite of complex karyotypes. Of the patients (12) negative for both FLT3 and NPM1 mutations, three patients showed complete response to IC. Conclusion: In general, African-American patients had poor response to IC. All patients with NPM1 mutation had complete response to IC. Patients with FLT3 mutation but without NPM1 mutation were all unresponsive to IC, while those with both FLT3 and NPM1 mutations had complete response to IC and have remained in remission. Contrary to prevailing concept, we found NPM1 mutation to be associated with favorable outcome to IC even in patients with positive FLT3.